2010
DOI: 10.1111/j.1574-6968.2010.02013.x
|View full text |Cite
|
Sign up to set email alerts
|

The Scl1 of M41-type group A Streptococcus binds the high-density lipoprotein

Abstract: Streptococcal collagen-like protein 1 (Scl1) is a virulence factor on the surface of group A Streptococcus (GAS). We have previously reported that several Scl1 proteins derived from various M-type GAS strains, including M41, can bind to low-density lipoprotein but Scl1 protein derived from M6-type GAS strain can not. Here, we demonstrated that recombinant protein, designated C176, derived from Scl1.41 of GAS M41-type strain also binds both plasma and purified high-density lipoprotein (HDL). Next, we determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…The two S. pyogenes bacterial collagens, Scl1 and Scl2, have sequences indicating they are anchored on the cell surface and have been shown to bind to a variety of host proteins. Depending on the specific serotype, the non-collagenous V-domain of Scl1 may bind to high-density lipoprotein (HDL) (Gao et al 2010), low-density lipoprotein (LDL) (Han et al 2006a), factor H (Caswell et al 2008a), complement factor H-related protein 1 (CFHR1) (Reuter et al 2010), or the extra cellular matrix (ECM) proteins fibronectin and laminin (Caswell et al 2009). Binding to these components helps S. pyogenes escape from complement-regulated phagocytosis and enhances its adherence to the macrophages and ECM.…”
Section: Biological Role Of Bacterial Collagen-like Proteinsmentioning
confidence: 99%
“…The two S. pyogenes bacterial collagens, Scl1 and Scl2, have sequences indicating they are anchored on the cell surface and have been shown to bind to a variety of host proteins. Depending on the specific serotype, the non-collagenous V-domain of Scl1 may bind to high-density lipoprotein (HDL) (Gao et al 2010), low-density lipoprotein (LDL) (Han et al 2006a), factor H (Caswell et al 2008a), complement factor H-related protein 1 (CFHR1) (Reuter et al 2010), or the extra cellular matrix (ECM) proteins fibronectin and laminin (Caswell et al 2009). Binding to these components helps S. pyogenes escape from complement-regulated phagocytosis and enhances its adherence to the macrophages and ECM.…”
Section: Biological Role Of Bacterial Collagen-like Proteinsmentioning
confidence: 99%
“…3A, top panel). To prevent the possibility of serum proteins binding to Scl-1 (21,22,(25)(26)(27) and affecting phagocytosis, bacteria were not preop-sonized or incubated in the presence of human serum during phagocytosis assays or subsequent in vitro cell-based assays. Control treatment of the neutrophils with cyt D to prevent phagocytosis effectively eliminated the fluorescent signal and validated our assay specificity (Fig.…”
Section: Scl-1 Is Important For Bacterial Persistence In a Mouse Modementioning
confidence: 99%
“…In other, less virulent GAS serotype strains, Scl-1 has been shown to participate in biofilm formation (16,17), attachment to extracellular matrix proteins (18), and attachment to lung epithelial cells (15,19,20) but not pharyngeal cells (14). Studies using recombinant Scl-1 have shown that the protein, via its serotype-hypervariable N terminus, can bind a variety of host proteins, including serum lipoproteins (21,22), integrins (23,24), the complement inhibitors FH and FH-related protein 1 (25,26), and the thrombin-activatable fibrinolysis inhibitor (27). While Scl-1 proteins of different GAS serotypes bind a variety of host proteins, the results suggest a common role for Scl-1 in perturbing the functions of the innate immune system.…”
mentioning
confidence: 99%
“…It has been demonstrated that Scl1 can bind selected human extracellular matrix components [109], cellular integrin receptors [107,118,119], and plasma components [120-122]. Importantly, human collagen receptors such as integrins α2β1 and α11β1 recognize the triple helix CL domain of Scl1, and this event results in cell signaling [107,118,119].…”
Section: Bacterial Collagen Triple Helix As a Bait For Host-pathogen mentioning
confidence: 99%